Meta-omic profiling reveals ubiquity of genes encoding for the nitrogen-rich biopolymer cyanophycin in activated sludge microbiomes - Farmer, McKenna; Rajasabhai, Rashmi; Tarpeh, William; Tyo, Keith; Wells, George (Frontiers in Microbiology, 2023)
Recovering nitrogen (N) from municipal wastewater is a promising approach to prevent nutrient pollution, reduce energy use, and transition towards a circular N bioeconomy, but remains a technologically challenging endeavor. Existing N recovery techniques are optimized for highstrength, low-volume wastewater. Therefore, developing methods to concentrate dilute N from mainstream wastewater will bridge the gap between existing technologies and practical implementation. The N-rich biopolymer cyanophycin is a promising candidate for N bioconcentration due to its pH-tunable solubility characteristics and potential for high levels of accumulation. However, the cyanophycin synthesis pathway is poorly explored in engineered microbiomes. In this study, we analyzed over 3700 publicly available metagenome assembled genomes (MAGs) and found that the cyanophycin synthesis gene cphA was ubiquitous across common activated sludge bacteria. We found that cphA was present in common phosphorus accumulating organisms (PAO) Ca. 'Accumulibacter' and Tetrasphaera, suggesting potential for simultaneous N and P bioconcentration in the same organisms. Using metatranscriptomic data, we confirmed the expression of cphA in lab-scale bioreactors enriched with PAO. Our findings suggest that cyanophycin synthesis is a ubiquitous metabolic activity in activated sludge microbiomes. The possibility of combined N and P bioconcentration could lower barriers to entry for N recovery, since P concentration by PAO is already a widespread biotechnology in municipal wastewater treatment. We anticipate this work to be a starting point for future evaluations of combined N and P bioaccumulation, with the ultimate goal of advancing widespread adoption of N recovery from municipal wastewater.